Retinal vasculature by optical coherence tomography angiography after YAG laser capsulotomy in non diabetic patients - Abokahla, Osama Abdelgalil; Ghoneim, Ehab Mahmoud; Mohamed, Mohamed Mounir (Indonesian Vitreoretinal Society, 2024)
Introduction: This study aimed to evaluate the effect of Neodymium-doped Yttrium Aluminum-Garnet (Nd: YAG) laser capsulotomy on retinal vessel perfusion densities and macular thickness using optical coherence tomography angiography (OCT-A). Methods: The study included 35 eyes of 35 participants with an average age of 70 years old. The participants having posterior capsule opacification were non-diabetic. The preoperative evaluation included history taking, ophthalmological examination and OCT-A was done. All patients underwent YAG laser posterior capsulotomy and then macular thickness and retinal microvascular changes were assessed at one month using OCT-A. Results: There was significant improvement of Best Corrected Visual Acuity (BCVA) (Decimal) post laser capsulotomy (P< 0.001), No significant change was determined before and after capsulotomy in macular thickness measurements, and Perfusion density in parafovea and perifovea layers. (All p > 0.05). Conclusion: Nd-YAG laser capsulotomy for posterior capsule opacification is considered to be a safe procedure and has no visible effect on macular thickness measurements, flow areas, and vessel perfusion densities.